High Reliefs from 3D Scenes. (May 2015) - Arpa, Sami; Süsstrunk, Sabine; Hersch, Roger D.
Abstract We present a method for synthesizing high reliefs, a sculpting technique that attaches 3D objects onto a 2D surface within a limited depth range. The main challenges are the preservation of distinct scene parts by preserving depth discontinuities, the fine details of the shape, and the overall continuity of the scene. Bas relief depth compression methods such as gradient compression and depth range compression are not applicable for high relief production. Instead, our method is based on differential coordinates to bring scene elements to the relief plane while preserving depth discontinuities and surface details of the scene. We select a user‐defined number of attenuation points within the scene, attenuate these points towards the relief plane and recompute the positions of all scene elements by preserving the differential coordinates. Finally, if the desired depth range is not achieved we apply a range compression. High relief synthesis is semi‐automatic and can be controlled by user‐defined parameters to adjust the depth range, as well as the placement of the scene elements with respect to the relief plane.